CITARASA JAJAN PASAR YOGYAKARTA DALAM DESAIN GRAFIS - Hartono Karnadi (SURYA SENI, 2007)
People in Yogyakarta truly respect cultural inheritance and the ancestors’ tradition. The existence of Yogyakarta Palace truly supports the development of its culture. The various kinds of traditional events continually develop in the society, such as marriage, pregnancy, birth ceremony, and so forth. On thoseevents, there will be speciﬁ c snacks and meal that are often called as “sesaji”. One of them is “jajan pasar”. In fact, “jajan pasar” that develops in the society is very unique and varied.In spite of the fact of many reasons, there are things which are difﬁ cult to ﬁ nd or no longer produced anymore, furthermore some kinds of snack are no longer available and consequently forgotten. Regarding to above mentioned problems it is necessary to do research and documenting such ‘jajan pasar’ as complement to a number of books of food making which are mostly exposing modern food recipes. As a matter of fact publication on Yogyakartan traditional food-making and recipes is very rare, ifnot available.This book entitled entitled “Citarasa Jajan Pasar Yogyakarta” (Flavour of Yogyakartan ordinary snacks) is one of the efforts to preserve cultural heritage of Yogyakarta. The design of the book not only cover the aesthetic and functional aspects to promote the jajan pasar as cultural heritage to preserve, but also taps visual potentials of the food as graphic elements to communicate.Keywords: Jajan pasar, cultural heritage.